Phase equilibria in ternary mixtures of methyl oleate, glycerol, and methanol - Andreatta, Alfonsina Ester (2008)
Transesterification reactions are common in the production of some important chemicals, such as biodiesel and mono- and diglycerides. Knowledge of the phase equilibrium conditions of the reactive mixture is essential to explore possible operating conditions for the reactor and the downstream separation process. In this work, liquid-liquid and vapor - liquid - liquid equilibrium data have been measured for the ternary system methyl oleate - methanol - glycerol, at temperatures between 313 and 393 K. The group contribution wim association equation of state (GCA-EOS) and the A-UNIFAC model were applied to represent the phase equilibria of dus ternary system. Self-association in glycerol and methanol and cross-association with methyl esters were taken into account. © 2008 American Chemical Society.